Public Services In Ngalam Baru Village Government, Gumay Talang District, Lahat District In The Paradigm Of Good Governance - Miki Effendi; Fierda Nurany (Gayaku Publisher, 2022)
This research aims to describe public services in the government offices of Ngalam Baru Village, Gumay Talang District, Lahat Regency in the Good Governance Paradigm. In general, public service is an action aimed at providing benefits to other people, individuals, and community groups, by providing needs to the community that has been identified in the organization as a service center that operates centrally in the village without reducing it. The research method used is a qualitative approach. The focus of this research is the service at the Ngalam Baru Village government office. This study used data collection techniques through field observations and documentary observations. The documents collected are documents relevant to the problem and this research focuses on public services at the Ngalam Baru Village Government Office in 2022. Documentation is used by researchers to obtain accurate and objective data references. Thus the results of the research that has been carried out, that public services at the Ngalam Baru Village Office, Gumay Talang District, Lahat Regency are still not optimal, the reason is the lack of implementation of the SOP (Standard Operating Procedure) that has been set by the government. There are still many service officers in this case, village apparatus who cannot operate media devices in the form of computers, laptops, and notebooks.